Predictive power of renormalisation group flows: a comparison - Litim, Daniel F.; Pawlowski, Jan M. (Physics letters, 2001)
We study a proper-time renormalisation group, which is based on an operator cut-off regularisation of the one-loop effective action. The predictive power of this approach is constrained because the flow is not an exact one. We compare it to the Exact Renormalisation Group, which is based on a momentum regulator in the Wilsonian sense. In contrast to the former, the latter provides an exact flow. To leading order in a derivative expansion, an explicit map from the exact to the proper-time renormalisation group is established. The opposite map does not exist in general. We discuss various implications of these findings, in particular in view of the predictive power of the proper-time renormalisation group. As an application, we compute critical exponents for O(N)-symmetric scalar theories at the Wilson-Fisher fixed point in 3d from both formalisms.
Gesehen am 06.12.2017